Volumetric analysis of small bowel motility in an unselected cohort of patients with Crohn's disease. Issue 10 (29th May 2020) - Dreja, Julia; Ekberg, Olle; Leander, Peter; Månsson, Sven; Ohlsson, Bodil
Abstract: Background: Quantified terminal ileal motility during magnetic resonance enterography (MRE) has been suggested to be used as a biomarker of Crohn's disease (CD). The aim of the present study was to evaluate this method in clinical practice. Methods: Healthy volunteers and all consecutive patients referred to MRE during a 2‐year period were asked to participate and complete the Irritable Bowel Syndrome‐Symptom Severity Scale (IBS‐SSS) to assess gastrointestinal symptoms. Medical records were scrutinized, and motility indices (MIs) were calculated from MR images. Key Results: Twenty‐two healthy controls and 134 examinations with CD were included (inclusion rate: 76.3%). Patients with CD had increased mural thickness of the terminal ileum, increased fecal calprotectin, and more symptoms than controls. Patients with active CD had increased mural thickness of ileum and terminal ileum, higher MR activity indices, and signs of inflammation in laboratory analyses, but similar symptoms, compared with inactive disease. After exclusion of sole colon disease (n = 13), MI inversely correlated with mural thickness in terminal ileum, and MI was lower in active disease versus controls in ileum ( P = .019) and terminal ileum ( P = .005), and versus inactive disease in terminal ileum ( P = .044). The area under the curve of MI in terminal ileum was 0.736 for active CD against healthy controls ( P = .002) and 0.682 for active against inactive CD ( P = .001). MIs were similar in controls and inactive CD. Conclusions and Interferences: MI reflects inflammatory activity in the intestine. Alterations in MI did not explain symptomatology in inactive CD, without measurable inflammatory parameters in morphology or laboratory analyses. Abstract : Inclusion of healthy volunteers and all consecutive patients referred for magnetic resonance enterography during a 2‐year period. Motility indices were calculated and related to clinical signs and symptoms. 22 healthy controls and 134 examinations of patients with Crohn's disease were enrolled. Motility index was lower in ileum and terminal ileum in patients compared with controls, which correlated inversely with mural thickness in the terminal ileum. There was no correlation between bowel symptoms and motility index.